2022
DOI: 10.3390/mi13030426
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Conjugated Magnetic Beads for Sperm Sexing Using a Multi-Wall Carbon Nanotube Microfluidic Device

Abstract: This study proposes a microfluidic device used for X-/Y-sperm separation based on monoclonal antibody-conjugated magnetic beads, which become positively charged in the flow system. Y-sperms were selectively captured via a monoclonal antibody and transferred onto the microfluidic device and were discarded, so that X-sperms can be isolated and commercially exploited for fertilization demands of female cattle in dairy industry. Therefore, the research team used monoclonal antibody-conjugated magnetic beads to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Subsequently, a patterned substrate known as the “master” is created using expensive techniques, which offer excellent resolution. These techniques include photolithography (250 nm), nanoimprint lithography (15 nm), x-ray lithography (15 nm), or electron beam lithography (10 nm), but are primarily used in large-scale manufacturing facilities ( Maldonado & Peckerar, 2016 ; Gale et al, 2018 ; Thuau et al, 2018 ; Matsumoto et al, 2020 ; Phiphattanaphiphop et al, 2022 ). Consequently, there has been a growing interest in employing low-cost manufacturing techniques, including micromilling (25 μm), 3D printing (5–100 μm), and laser cutting (25 μm) ( Gale et al, 2018 ; Rusling, 2018 ; Hamilton et al, 2021 ; Šakalys et al, 2021 ; Preetam et al, 2022 ; Qin S et al, 2022 ).…”
Section: Manufacturing Techniquesmentioning
confidence: 99%
“…Subsequently, a patterned substrate known as the “master” is created using expensive techniques, which offer excellent resolution. These techniques include photolithography (250 nm), nanoimprint lithography (15 nm), x-ray lithography (15 nm), or electron beam lithography (10 nm), but are primarily used in large-scale manufacturing facilities ( Maldonado & Peckerar, 2016 ; Gale et al, 2018 ; Thuau et al, 2018 ; Matsumoto et al, 2020 ; Phiphattanaphiphop et al, 2022 ). Consequently, there has been a growing interest in employing low-cost manufacturing techniques, including micromilling (25 μm), 3D printing (5–100 μm), and laser cutting (25 μm) ( Gale et al, 2018 ; Rusling, 2018 ; Hamilton et al, 2021 ; Šakalys et al, 2021 ; Preetam et al, 2022 ; Qin S et al, 2022 ).…”
Section: Manufacturing Techniquesmentioning
confidence: 99%
“…[ 40 ] Multiwall carbon nanotubes have also been used in microfluidic platforms for sperm sexing, exhibiting 80.12% microcirculation. [ 41 ] Li et al. reported a double‐helix microfiber coupler coated with graphene oxide as a microfluidic platform, with a low detection limit and high sensitivity.…”
Section: Microfluidic Biosensors For Biomarker Detectionmentioning
confidence: 99%
“…[40] Multiwall carbon nanotubes have also been used in microfluidic platforms for sperm sexing, exhibiting 80.12% microcirculation. [41] Li et al reported a double-helix microfiber coupler coated with graphene oxide as a microfluidic platform, with a low detection limit and high sensitivity. [42] In recent years, several semiconductor nanomaterials, due to their excellent fluorescence properties, have been widely used to construct microfluidic fluorescence biosensors.…”
Section: Microfluidic Fluorescence Biosensorsmentioning
confidence: 99%